THE ROLE OF AUDIT COMMITTEE CHARACTERISTICS AND AUDIT QUALITY IN IMPROVING EARNINGS QUALITY - Ika Rachmawati; Jacobus Widiatmoko; MG. Kentris Indarti (Faculty of Economic and Business Universitas STIKUBANK, 2022)
The purpose of this study was to examine the effect of the effectiveness of the audit committee, as measured by committee size, number of meetings, and competence, as well as audit quality on earnings quality with firm size, leverage, and profitability as control variables. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample selection method used purposive sampling and 292 data were obtained. The results of hypothesis testing with multiple linear regression showed that the size of the audit committee and audit quality had a positive effect on earnings quality. Meanwhile, the number of meeting and competence has no effect on the quality of earnings. Furthermore, all control variables affect earnings quality.